FERRAMENTA ONLINE: UMA PROPOSTA PARA INVESTIGAÇÃO SOBRE FISSURAS LABIOPALATINAS - Menon, Lorena Cristina (2016)
Introduction: The research carried out with the help of the Internet are becoming increasingly popular among researchers, mainly due to its advantages of lower cost, speed and the ability to reach specific populations. Can be considered very similar, methodologically, the research carried out using self-administered questionnaires, differing only in how they are conducted. Instruments to measure specific knowledge can be useful in public health policies. Objective: To present an assessment tool of health professionals knowledge about cleft lip and palate. Methodology: This is a descriptive exploratory study for construction and standardization of an online questionnaire. The survey covered all nurses and paediatricians recorded in the respective Boards of Paraná State Regional. The study was conducted for the construction of an original multi-theme questionnaire from a comprehensive literature review. Consisting of a total of nineteen questions, eighteen multiple-choice and a dissertation. The questionnaire was introduced in google docs forms platform and sent via email to the Regional Councils of the categories to be disseminated to the email addresses of registered professionals. Data analysis was performed using descriptive statistics provided by the Google docs forms platform. Results: The total number of questionnaires sent was 20,637, with 18,476 for nurses and 2,161 for paediatricians. These were received 586 valid responses, of which 94% (n = 552) were nurses and 6% (n = 34) of paediatricians. Final Thoughts: The methodology used was appropriate to the purpose of the study and enabled the tool presented content validation. The questionnaire allowed the survey of health professionals concepts of cleft lip and palate and provided guiding data reinforce the importance of qualified training of health staff that welcomes the newly born with cleft lip and palate.